ANALISIS PEMBENTUKAN KARAKTER ANAK USIA DINI PADA KURIKULUM SEKOLAH ALAM - Ita Loka; Aan Listiana (IKIP Siliwangi, 2022)
Education in Indonesia has not yet been able to form a strong character, so that various schools have emerged, one of which is a natural school that can shape character in early childhood. Character emerges from the curriculum implemented in natural schools. This study aims to de- termine what character formation occurs in children in various natural schools. The method used is systematic review with thematic data analysis techniques. The database used to search for several sources is Google Scholar. The initial search that the author did obtained 20 journals and was selected based on exclusive criteria by looking at research objectives, research meth- ods, language, characters that appeared and related to natural schools so that the identified jour- nals were found to be quite closely related to natural schools and character building based on the curriculum used. The results of this study indicate that many characters are formed, namely leadership, religious, business spirit (entrepreneurship), love of nature and independence. The formation of this character is inseparable from the curriculum used and habituation in daily ac- tivities. The formation of character in children can also be seen from the culture that exists in natural schools. There are four main curricula used in character building, namely the Moral cur- riculum, the Science curriculum, the Leadership curriculum and the Entrepreneurship curricu- lum. In addition to the four curricula, there are also schools that use a combination of curricula from the National Education Office and natural schools.Pendidikan di Indonesia masih belum dapat membentuk karakter yang kuat, sehingga bermunculan sekolah-sekolah yang beraneka ragam salah satunya sekolah alam yang dapat membentuk karakter pada anak usia dini. Karakter muncul dari kurikulum yang diterapkan di sekolah alam. Penelitian ini bertujuan untuk mengetahui pembentukan karakter apa yang terjadi pada anak di berbagai sekolah alam. Metode yang digunakan sistematik review dengan teknik analisis data tematik. Database yang digunakan untuk mencari beberapa sumber adalah Google Scholar. Pencarian awal yang penulis lakukan didapatkan 20 jurnal dan diselesksi berdasarkan kriteria ekslusif dengan melihat tujuan penelitian, metode penelitian, bahasa, karakter yang muncul dan terkait sekolah alam sehingga didapatkan jurnal yang diidentifikasi berkaitan cukup erat dengan sekolah alam dan pembentukan karakter berdasarkan kurikulum yang digunakan. Hasil penelitian ini menunjukkan bahwa banyak karakter yang terbentuk yaitu leadership, reli- gious, jiwa bisnis (wirausaha), cinta alam dan mandiri. Pembentukan karakter tersebut tidak terlepas dari kurikulum yang digunakan dan pembiasaan dalam kegiatan sehari-hari. Pemben- tukan karakter pada anak juga dapat terlihat dari budaya yang ada di sekolah alam. Terdapat empat kurikulum utama yang digunakan dalam pembentukan karakter yaitu kurikulum Akhlak, kurikulum Sains, kurikulum Leadership dan kurikulum Entrepreneurship. Selain empat kuriku- lum itu ada juga yang sekolahnya menggunakan gabungan kurikulum dari Diknas dan sekolah alam.